Jerome's Hebrew philology : a study based on his commentary on Jeremiah - Graves, Michael, 1973- (Vigiliae Christianae, Supplements, 2007)
St Jerome (ca. 347-419), translator and prolific commentator on the Old Testament, left a lasting and controversial mark on the history of biblical scholarship through his radical return to the hebraica veritas , the 'Hebrew truth.' Yet, the extent of Jerome's Hebrew knowledge has been debated, and the actual role of Hebrew in Jerome's biblical exegesis has been little explored. This book shows how Jerome's Hebrew philology developed out of his training in classical literary studies, describes the nature of Jerome's command of Hebrew in light of his historical context and his use of Jewish sources, and explains how Jerome used Hebrew scholarship in his biblical interpretation. Jerome emerges as a competent Hebraist, limited by his context, yet producing work of enduring significance.